Rethinking Security in Nigeria : Conceptual Issues in the Quest for Social Order and National Integration - Ujomu, Philip Ogo; Adelugba, Dapọ (Book collections on Project MUSE., 2008)
Rethinking Security in Nigeria adopts an alternate conceptual and methodological framework for rethinking national security in Nigeria by using the humanities' multidisciplinary perspective against the backdrop of the hitherto restrictive analysis of the nature of national security. By expounding the largely unexplored cosmological, conceptual, ethical and aesthetic dimensions as key contributors to national survival and social integration, the volume argues systematically for a basic redefinition of the meanings of security, the value of life, government action and social re-engineering in order to create a new system of social order an integration. The authors attempt to extend the boundaries of previous theorizing on security by identifying alternate ethical and aesthetic approaches to national reconciliation and human development in present-day Nigeria, which faces major security challenges requiring the clarification of the basis for developing a just and harmonious society. The study is a contribution to the quest for defining the vital socio-cultural norms and doctrinal imperatives needed for responsible cooperative human action. It examines the roles of dominant works of philosophy, literature, plays and performances in the creation of a basis for political stability and social reconciliation in the society. It extends the boundaries of previous aesthetic studies and redefines the roles of ethics and aesthetics as crucial contributors to security, human development and world civilisation.